Porphyrin biosynthesis in soybean callus tissue system. Isolation, purification and general properties of δ-aminolaevulinate dehydratase - Tigier, H.A. (1968)
Fil:Tigier, H.A. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.